The Covenant of Water - Verghese, Abraham, 1955-; Verghese, Thomas; Lubikowski, Martin (New York : Grove Press, 2023)
"From the New York Times-bestselling author of Cutting for Stone comes a stunning and magisterial epic of love, faith, and medicine, set in Kerala, South India, following three generations of a family seeking the answers to a strange secret. The Covenant of Water is the long-awaited new novel by Abraham Verghese, the author of the major word-of-mouth bestseller Cutting for Stone, which has sold over 1.5 million copies in the United States alone and remained on the New York Times bestseller list for over two years. Spanning the years 1900 to 1977, The Covenant of Water is set in Kerala, on South India's Malabar Coast, and follows three generations of a family that suffers a peculiar affliction: in every generation, at least one person dies by drowning-and in Kerala, water is everywhere. At the turn of the century, a twelve-year-old girl from Kerala's long-existing Christian community, grieving the death of her father, is sent by boat to her wedding, where she will meet her forty-year-old husband for the first time. From this unforgettable new beginning, the young girl--and future matriarch, known as Big Ammachi--will witness unthinkable changes over the span of her extraordinary life, full of joy and triumph as well as hardship and loss, her faith and love the only constants. A shimmering evocation of a bygone India and of the passage of time itself, The Covenant of Water is a hymn to progress in medicine and to human understanding, and a humbling testament to the difficulties undergone by past generations for the sake of those alive today. Imbued with humor, deep emotion, and the essence of life, it is one of the most masterful literary novels published in recent years"--
Includes bibliographical references.
Keywords: Families -- Fiction; Drowning -- Fiction; Kerala (India) -- Fiction; Glasgow (Scotland) -- Fiction; Historical fiction; Novels